The role of non-governmental organizations in the mental health area: differences in understanding - Zupančič Vesna; Pahor Majda (Sciendo, 2016)
The contribution's aim is highlighting the differences in understanding non-governmental organizations' (NGOs) role in the mental health area within the public support network for patients with mental health problems from various viewpoints, in order to achieve progress in supporting patients with mental health problems in local communities.